Long term use of eltrombopag in children with chronic immune thrombocytopenia: extended real life retrospective multicenter experience of the Italian Association of Pediatric Hematology and Oncology - Giordano, Paola; Lassandro, Giuseppe; Barone, Angelica; Cesaro, Simone; Fotzi, Ilaria; Giona, Fiorina; Gorio, Chiara; Maggio, Angela; Miano, Maurizio; Marzollo, Antonio; Nardi, Margherita; Pession, Andrea; et al. (Frontiers in Medicine, 2023)
Background: The present multicenter retrospective study on eltrombopag administration in Italian children with chronic ITP aims to extend follow-up of our previous study. Materials and methods: This retrospective multicenter study was conducted in 17 centers affiliated to the Italian Association of Pediatric Haematology and Oncology (AIEOP). Patients were classified into three subgroups: group 1 included patients who discontinued treatment due to a stable platelet count; group 2 included patients who discontinued treatment due to ineffectiveness; group 3 included patients who did not permanently discontinue treatment. Results: 56 patients were eligible for analysis. The median duration of eltrombopag treatment was 40 months (7-71 months). Twenty patients (36%) discontinued permanently eltrombopag. The reasons of permanent discontinuation were adverse effects (n =1), inefficacy (n=10), stable platelet count (n=9). All patients of group 1 maintained a durable response without additional treatments after eltrombopag discontinuation. We found that patients of group 2 were on treatment for less time (median treatment time: 13,5 months, min: 6.0 – max: 56.0) than patients of group 1 (median treatment time: 34 months, min: 16.0 – max: 62.0) (p < 0.05). Patients of group 2 mostly did not achieve a stable platelet count in the first six months of treatment and underwent concomitant therapies during follow-up respect of group 1 and group 3 (p < 0.01) Conclusion: Our study found that the benefits of eltrombopag treatment, in terms of platelet count improvement and use of additional therapies, are identifiable from the first six months of treatment.